2012
DOI: 10.12659/msm.882731
|View full text |Cite
|
Sign up to set email alerts
|

Gastroesophageal reflux disease and pulmonary function: A potential role of the dead space extension

Abstract: SummaryBackgroundTo evaluate the differences in the existence and size of dead space in patients with and without Gastroesophageal Reflux Disease (GERD and non-GERD) expressed through the size of intrapulmonary shunt (QS/QT).Material/MethodsThe study enrolled 86 subjects – 43 patients referred for endoscopy because of symptoms of GERD (heartburn, acid regurgitation, dysfagia) and 43 healthy subjects with similar anthropometric characteristics without GERD symptoms. Based on endoscopy findings, patients were cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
8
0
1
Order By: Relevance
“…Mise et al [ 30 ] reported lower DLCO in patients with recently diagnosed GERD in comparison with healthy controls. Bonacin et al [ 31 ] showed statistically significant increases in FVC in the GERD group as compared with the non-GERD group. Among the GERD group, values of DLCO and DLCO/VA were significantly lower, and intrapulmonary shunt was significantly higher in comparison with the non-GERD group, which confirmed the correlation between GERD and damaged lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Mise et al [ 30 ] reported lower DLCO in patients with recently diagnosed GERD in comparison with healthy controls. Bonacin et al [ 31 ] showed statistically significant increases in FVC in the GERD group as compared with the non-GERD group. Among the GERD group, values of DLCO and DLCO/VA were significantly lower, and intrapulmonary shunt was significantly higher in comparison with the non-GERD group, which confirmed the correlation between GERD and damaged lung function.…”
Section: Discussionmentioning
confidence: 99%
“…Observational studies have suggested an association between risk factors for microaspiration (eg obesity, GERD, and diabetes mellitus) and development of serious hospital‐acquired conditions such as ARDS and HAP. Beyond its association with ARDS and HAP, microaspiration can also result in bronchospasm, and hypoxia during intubation . In this context, interventions that may be employed to reduce the risk of microaspiration are clearly of great interest.…”
Section: Discusssionmentioning
confidence: 99%
“…Macroaspiration (grossly visible aspiration) has been clearly associated with severe pulmonary injury . More recently, microaspiration (aspiration without grossly visible gastric material) has also been associated with significant morbidity including acute respiratory distress syndrome (ARDS), ventilator associated pneumonia (VAP), and acute respiratory failure due to bronchoconstriction and ventilation‐perfusion mismatching …”
Section: Introductionmentioning
confidence: 99%
“…A higher frequency of proximal GERs is in line with findings from other studies (Embarak et al 2015;Gao et al 2015;Savarino et al 2013). It has been observed that pulmonary function, as represented, for instance, by carbon monoxide diffusion lung capacity (DL CO ) and carbon monoxide diffusion lung capacity per unit alveolar volume (DL CO /VA) measurements, is appreciably lower in GERD patients (Bonacin et al 2012;Mise et al 2010). It is possible that microaspirations cause surfactant damage, which stimulates the development of an intrapulmonary shunt.…”
Section: Discussionmentioning
confidence: 99%